2016
DOI: 10.1007/s11222-016-9687-5
|View full text |Cite
|
Sign up to set email alerts
|

A computationally efficient nonparametric approach for changepoint detection

Abstract: In this paper we build on an approach proposed by for nonparametric changepoint detection. This approach defines the best segmentation for a data set as the one which minimises a penalised cost function, with the cost function defined in term of minus a non-parametric loglikelihood for data within each segment. Minimising this cost function is possible using dynamic programming, but their algorithm had a computational cost that is cubic in the length of the data set. To speed up computation, resorted to a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 41 publications
0
83
0
Order By: Relevance
“…For change point detection in the mean, the selected competitors from the Comprehensive R Archive Network are changepoint (Killick and Eckley, 2014;Killick et al, 2016) implementing the PELT methodology that was proposed by Killick, Fearnhead and Eckley (2012), changepoint.np implementing a non-parametric extension of the PELT methodology that was studied in Haynes et al (2017), wbs (Baranowski and Fryzlewicz, 2015) implementing WBS proposed by Fryzlewicz (2014), ecp (James and Matteson, 2014) implementing the e.cp3o method that was proposed by James and Matteson (2015), strucchange (Zeileis et al, 2002) implementing the methodology of Bai and Perron (2003), Segmentor3IsBack (Cleynen et al, 2013) implementing the technique that was proposed by Rigaill (2015), nmcdr (Zou and Lancezhange, 2014) implementing NMCD, the non-parametric multiple change point detection methodology of , stepR (Pein et al, 2018) implementing the simultaneous multiscale change point estimator SMUCE that was proposed by Frick et al (2014) and FDRSeg (Li et al, 2017) implementing the method called FDRSeg proposed by Li et al (2016). We refer to the corresponding methods as PELT, NP-PELT, WBS, e.cp3o, B&P, S3IB, NMCD, SMUCE and FDRSeg respectively.…”
Section: Estimatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…For change point detection in the mean, the selected competitors from the Comprehensive R Archive Network are changepoint (Killick and Eckley, 2014;Killick et al, 2016) implementing the PELT methodology that was proposed by Killick, Fearnhead and Eckley (2012), changepoint.np implementing a non-parametric extension of the PELT methodology that was studied in Haynes et al (2017), wbs (Baranowski and Fryzlewicz, 2015) implementing WBS proposed by Fryzlewicz (2014), ecp (James and Matteson, 2014) implementing the e.cp3o method that was proposed by James and Matteson (2015), strucchange (Zeileis et al, 2002) implementing the methodology of Bai and Perron (2003), Segmentor3IsBack (Cleynen et al, 2013) implementing the technique that was proposed by Rigaill (2015), nmcdr (Zou and Lancezhange, 2014) implementing NMCD, the non-parametric multiple change point detection methodology of , stepR (Pein et al, 2018) implementing the simultaneous multiscale change point estimator SMUCE that was proposed by Frick et al (2014) and FDRSeg (Li et al, 2017) implementing the method called FDRSeg proposed by Li et al (2016). We refer to the corresponding methods as PELT, NP-PELT, WBS, e.cp3o, B&P, S3IB, NMCD, SMUCE and FDRSeg respectively.…”
Section: Estimatorsmentioning
confidence: 99%
“…A non‐parametric version of the PELT method was investigated by Haynes et al . (). Another general approach is based on the idea of binary segmentation (BS) (Vostrikova, ), which can be viewed as a greedy approach with a limited computational cost.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Precisely, for two indexes t and s (t < s < T ), the pruning rule is given by: An extension of Pelt is described in [9] to solve the linearly penalized change point detection for a range of smoothing parameter values [β min , β max ]. Pelt has been applied on DNA sequences [16,17], physiological signals [89], and oceanographic data [111].…”
Section: Solution To Problem 2 (P2): Peltmentioning
confidence: 99%
“…If p is small, we may not want to make the Normal assumption. In this case, we recommend using a non-parametric test statistic, such as the empirical distribution from Zou et al (2014) (where consistency has also been shown) as embedded within PELT in Haynes et al (2017b).…”
Section: Analyzing Mapped Time Seriesmentioning
confidence: 99%